2019
DOI: 10.1038/s41467-019-09733-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation of macrophages by dynamic ligand presentation via ligand–cation coordination

Abstract: Macrophages regulate host responses to implants through their dynamic adhesion, release, and activation. Herein, we employ bisphosphonate (BP)-coated gold nanoparticle template (BNP) to direct the swift and convertible formation of Mg 2+ -functional Mg 2+ -BP nanoparticle (NP) on the BP-AuNP surface via reversible Mg 2+ -BP coordination, thus producing (Mg 2+ -BP)-Au dimer (MgBNP). Ethylenediaminetetraacetic acid-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 36 publications
0
70
0
Order By: Relevance
“…According to previous reports, manipulating cell adhesive ligands to formulate proper nanotopography is able to control macrophage polarization directions. 40,41 Therefore, our implant surface may have influenced the cell adhesion organization, thus resulting in ERK pathway activation.…”
Section: Dovepressmentioning
confidence: 99%
“…According to previous reports, manipulating cell adhesive ligands to formulate proper nanotopography is able to control macrophage polarization directions. 40,41 Therefore, our implant surface may have influenced the cell adhesion organization, thus resulting in ERK pathway activation.…”
Section: Dovepressmentioning
confidence: 99%
“…They found that immobilized Wnt5a mimetic ligand-activated noncanonical Wnt signaling leading to enhanced intracellular calcium level, F-actin stability, actomyosin contractility, and cell adhesion structure development [40]. Kang et al (2019) suggested that macrophages play a significant role in regulating foreign body response in biomaterials. The macrophages in biomaterials can reversibly convert their cell adhesion and promote the tissue healing processes by regulating the inflammatory of tissues [41].…”
Section: Introductionmentioning
confidence: 99%
“…The bio‐functionalization of developed biomaterials was conducive to further enhance its bioactivity. It is well known that surface nanostructures or decoration of bioactive motifs could regulate cells behaviours, and greatly improve the potential of cell differentiation, which is the key factor to the success of the implanted scaffolds 17,44,45 . For example, a noncanonical Wnt5a motif could functionalize biomaterials in enhancing the osteogenesis and associated skeleton formation 44 .…”
Section: Discussionmentioning
confidence: 99%